Brazilian Breast Cancer Care Network: the perspective of health managers - Rosely Erlach Goldman; Elisabeth Niglio Figueiredo; Suzete Maria Fustinoni; Káren Mendes Jorge de Souza; Ana Maria de Almeida; Maria Gaby Rivero de Gutiérrez
ABSTRACT Objective: To analyze the organization of the Brazilian Breast Cancer Care Network, according to the perspective of managers of the Coordenadoria Regional de Saúde Sudeste (Southeast Regional Coordination of Health) of the city of São Paulo. Method: A descriptive study, with a qualitative approach, carried out with seven managers of this Coordination. The interview data were analyzed based on the components of the operational structure of the Brazilian Health Care Network: Communication Center; Secondary and Tertiary Care Points; Support Systems; Logistic Systems; and Network Governance System. Results: There is heterogeneity in the operationalization of the Care Network and the obstacles to its integration and comprehensiveness were: fragility of the bond with the users; high turnover of professionals in Primary Health Care; lack of standardization of the reference system and counter-referral, and low cooperation between municipal and state health services. Final considerations: The organization of the Brazilian Breast Cancer Care Network is fragmented, thus compromising the comprehensiveness of care.